Collaborative study to establish World Health Organization international reference reagents for dengue virus Types 1 to 4 RNA for use in nucleic acid testing. Issue 8 (26th June 2017) - Añez, Germán; Volkova, Evgeniya; Jiang, Zhen; Heisey, Daniel A. R.; Chancey, Caren; Fares, Rafaelle C.G.; Rios, Maria; ,
Abstract : BACKGROUND: Dengue is the most important reemerging mosquito‐borne viral disease worldwide. Caused by dengue virus (DENV), a member of the genus Flavivirus in the Flaviviridae family, dengue can be asymptomatic (approx. 80% of cases) or symptomatic, ranging from a flu‐like illness known as dengue fever, to a life‐threatening form called severe dengue. DENV is primarily transmitted from human to human through the bite of mosquitoes of the genus Aedes ; however, it is also transmissible by transfusion of blood and blood components and by solid organ transplant. Nucleic acid test (NAT) assays are considered the most appropriate approach for blood donor screening for recent DENV infections, but there is no Food and Drug Administration–approved assay for the screening of blood for DENV. STUDY DESIGN AND METHODS: An international collaborative study was conducted to assess the suitability of reference reagent (RR) candidates for DENV Types 1 to 4 RNA for use in NAT‐based assays. RESULTS: Two sets of RR candidates were prepared for each DENV type, one liquid frozen (Set 1) and one lyophilized (Set 2). A total of 28 laboratories from 20 countries agreed to participate in the study, of which 21 submitted the results for qualitative and/or quantitative assessments. CONCLUSION: The World Health Organization has established the lyophilized materials as international RRs for DENV RNA with a unitage of 13, 500, 69, 200, 23, 400, and 33, 900 units/mL for DENV‐1 to ‐4, respectively.